Why Women Suppress Women in Organizations: A Qualitative Study from Sydney - Du, Jiaxing; Yang, Zhifei (Journal of Theory and Practice in Humanities and Social Sciences, 2025)
This study investigates the phenomenon of women-to-women suppression in organizational contexts, a critical yet underexplored barrier to workplace gender equality. Drawing on Social Identity Theory and Foucauldian perspectives on power, we examine how female leaders may suppress the professional advancement of other women as a response to systemic pressures within male-dominated environments. Using qualitative data from 36 in-depth interviews with 18 female professionals across diverse industries, we identify key mechanisms of suppression, including exclusion from decision-making, inequitable resource distribution, and emotional manipulation. Our findings reveal that these behaviors are not merely individual choices but are deeply embedded in organizational cultures and gendered power hierarchies. By bridging individual agency and institutional structures, this research advances theoretical discourse on gender dynamics in organizations and offers actionable insights for fostering inclusive leadership and equitable workplace practices.